ANALISIS KOMPOSISI TUBUH MENGGUNAKAN BIOIMPEDANCE ANALYSIS (BIA) PADA PEMAIN FUTSAL CLUB BINTANG TIMUR SURABAYA - Suhendra, Sunny Rizky; Himawan, Agus; Purwoto, Septyaningrum Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the Body Composition Using Bioimpedance Analysis (BIA) in Futsal Players of Bintang Timur Club Surabaya. The method used is a survey method with test and measurement techniques to collect data. The sample in this study were all professional BTS FC players totaling 17 athletes. The average age of the sample was 25.47 years ± 4.81, average height 175.35 cm ± 6.19, average weight 72.12 kg ± 7.49, average BMI 23.41 kg / m2 ± 1.66, and average target weight 72.09 kg ± 6.51 indicating that BMI is included in the normal category. The average TBW results were 45.67 kg ± 4.64, average protein 12.49 kg ± 1.24, average mineral 4.28 kg ± 0.46, average SMM 35.72 kg ± 3.76, average PBF 13.25% ±4.38, average BMR 1718.53 Kcal ± 136.99, and average WHR 0.78 ±0.03 all in the normal category. The average results of FFM Right Arm 3.33 ± 0.43, average FFM Left Arm 3.32 ± 0.37, average FFM Trunk 26.42 ± 2.37, average BFM Right Arm 0.41 ± 0.22, average BFM Trunk 4.59 ± 2.04, average BFM Right Leg 1.59 ± 0.48, average BFM Left Leg 1.59 ± 0.49 overall in the normal category. The conclusion of this study was that the results of the athlete's BIA were normal and athletes needed to pay attention to the target of losing a little weight to achieve optimal performance.